Employee Engagement and Employee Performance; Mediating Knowledge Sharing - Conchita V. Latupapua; Pieter NR Rehatta; Frandyo I. Muskita (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of employee engagement on employee performance with knowledge sharing as a mediating variable. The population in this study were all employees of Perum BULOG Maluku Regional Office, totaling 50 people. The sampling technique was simple random sampling using the Slovin formula and a sample of 44 respondents was obtained. Data analysis was carried out using descriptive analysis and inferential analysis, the analysis tool used was Structural Equation Modeling (SEM) with the partial least squares (PLS) approach and using the SMARTPLS program. The results of this study indicate that there is a positive and significant effect of Employee Engagement on Knowledge Sharing, a positive and significant effect of Knowledge Sharing on Employee Performance,